RANCANG BANGUN SISTEM PENGINGAT TUGAS KULIAH BERBASIS WEB UNTUK MENINGKATKAN MANAJEMEN WAKTU MAHASISWA - Felix John Pardamean Hutabarat; Aqilah Defiyanti; Rani Indah Sari; Yuda Advis Ambrosius Sitohang; Adidtya Perdana (Jurnal Teknologi Informasi dan Komputer, 2025)
Students frequently encounter challenges in managing academic schedules and completing assignments on time due to the demanding nature of coursework and involvement in non-academic activities. Poor time management can adversely affect students' academic performance. Consequently, this study aims to design and develop a web-based academic task reminder system to assist students in managing schedules more effectively. The application is developed using HTML, CSS, and JavaScript, with data storage based on local storage, enabling users to access and store assignment information without requiring a server connection. The development methodology employed in this research follows the Software Development Life Cycle (SDLC) Waterfall model, which encompasses the stages of requirements analysis, system design, implementation, testing, and maintenance. Black Box testing was conducted to verify that all features—including task addition, deletion, sorting by deadline or alphabetically, and data storage—function as intended. Test results demonstrate that the system enhances task management efficiency and helps students organize schedules in a more structured manner. Furthermore, the system allows students to conveniently access task lists anytime and anywhere, eliminating the risk of data loss upon page refresh. Overall, this web-based task reminder system successfully fulfills user requirements in managing academic assignments more effectively, thereby fostering discipline and improving productivity in meeting academic deadlines.